IMPLEMENTASI METODE DEMPSTER SHAFER DALAM SISTEM PAKAR SCREENING PASIEN DENGAN HIPERKOLESTROLEMIA - Asminah Asminah (JUTIM (Jurnal Teknik Informatika Musirawas), 2021)
This study aims to produce an expert system that uses the Dempster Shafer method. The background of this research is that hypercholesterolemia can occur at the age of 20 to 65 years and many people do not know the symptoms of hypercholesterolemia so that people must come directly to the Bandar Inpatient Health Center (UPTD) to check these symptoms. An expert system is a computer-based application that is used to solve a problem as thought by an expert. The development model used is the Waterfall model which consists of analysis, design, coding, testing and maintenance. And the Testing Method used is Black Box Testing with a score of 3.7 from the expert review and 3.8 from the beta recapitulation implementation with a valid category. The Dempster Shafer method will be used in making this expert system. Based on the symptoms made, the largest confidence value is found in P1 with a value of 0.6780 x 100% = 67.8%. This method was chosen because this method is considered capable of providing a high level of confidence. This expert system is made using the PHP and MySQL programming languages. From the application of the Dempster Shafer method, this study resulted in an expert system for web-based screening of patients with hypercholesterolemia.